Glycosylation of bovine α-lactalbumin : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Biochemistry, at Massey University, New Zealand - Chandrika, Udumalagala Gamage (Massey University, 1999)
Bovine α-lactalbumin exists in four different forms. These are the F, M, S1 and S2 forms named after their positions on native gels. F, S1 and S2 are minor components representing 15% of the total α-lactalbumin fraction whereas M is the major component. S1 and S2 have been shown to be glycoforms of a-lactalbumin and although there are potentially three glycosylation sites in the protein, only asparagine 45 appears to be glycosylated. It has been suggested that F differs from M by the replacement of an amide group. The glycoforms of α-lactalbumin (S 1 and S 2 ), and the non-glycosylated proteins (M and F) were isolated and purified using selective precipitation, affinity chromatography, size exclusion chromatography and preparative electrophoresis. The potential glycosylation sites were investigated using selective proteolysis in conjunction with Edman sequencing and electrospray mass spectrometry (ES/MS). It was found that although the main fraction (M) or non-glycosylated protein contained no covalently bound carbohydrate, selected ion monitoring experiments showed that there appeared to be a lactosamine sugar associated with the protein. A number of methods were investigated for analysing and separating the glycoforms of α- lactalbumin. These included high pH anion exchange chromatography with pulsed amperometric detection (HPAEC/PAD), fluorophore assisted gel electrophoresis (FACE) and derivatisation of the oligosaccharides with l-(p-methoxy)phenyl-3-methyl-5-pyralozone (PMPMP) and subsequent separation by RP-HPLC. Electrospray mass spectrometry was used to confirm the results of these various techniques. Although it was not firmly established which of the three possible sites were glycosylated, refinement of the purification protocol resulted in several different glycans being identified on the basis of the ES/MS and FACE results. It would appear that there are up to 15 different glycoforms of α-lactalbumin, some of which are highly sialated. It is difficult to determine whether the simpler structures represent breakdown products of the more complex structures, or whether they are present naturally.
Keywords: Genetic aspects; Whey products; Glycosylation; Glycoproteins